Am I divine? - Göcke, Benedikt Paul (New blackfriars, 2010)
On the one hand, arguably, I am neither this nor that. Arguably, neither is God this or that – so, am I God? Otherwise it seems that I must be this and God must be that. On the other hand, the being of the universe is not something of which I could plausibly be construed as the ultimate cause. That is God's creative act. Because I do not create the universe, I am not God. So I am God and I am not God. Here's a solution: God is One but also Three, I am but one.